Calpains are activated by photodynamic therapy but do not contribute to apoptotic tumor cell death - Almeida, Ramiro D. (2004)
Photodynamic therapy (PDT) of cancer is a promising technique based on the formation of singlet oxygen following irradiation of a sensitizer with visible light. In the present work we investigated the role of calpains in PDT, using the human lymphoblastoid CCRF-CEM cells and bisulfonated aluminum phthalocyanine (AlPcS2) as a sensitizer. Photosensitization induced apoptotic cell death and a time-dependent activation of calpains, as determined using the fluorogenic substrate succinyl-Leu-Leu-Val-Tyr-7-amido-4-methylcoumarin (SLLVY-AMC). However, inhibition of calpains with calpain inhibitor II or with PD 150606 did not affect the demise process. The results indicate that although calpains are activated in PDT, they do not play a major role in tumor cell death.